Improving Landslide Susceptibility Using Groundwater Parameter in Samigaluh and Kalibawang Subdistricts - Susatio, Raja; Sartohadi, Junun; Samodra, Guruh; Setiawan, Muhammad Anggri; Wilopo, Wahyu (Geological Engineering Department Universitas Gadjah Mada, 2025)
Landslide susceptibility map is crucial in disaster risk management and it can be used for regional development plans. Landslide susceptibility map can be made by analyzing parameters that are assumed to affect landslides such as gradient slopes, geology, soil, and climate. Selection of landslide controlling parameters influences the accuracy of landslide susceptibility map. This study evaluates the effect of parameter that’s rarely used which is groundwater. The study area of this research was Kalibawang and Samigaluh Subdistricts, Kulonprogo, Special Region of Yogyakarta, Indonesia. Frequency ratio was used for the method along other parameters which is slope gradient, lithology, lineament density, land use, soil thickness. The result shows that groundwater parameter increase the accuracy by 22,29%. This study suggest that groundwater should be highly considered in landslide susceptibility mapping. In the other hand, groundwater depth mapping remains a challenge because most remote sensing method only detect shallow groundwater. Further research is necessary to develop better method for groundwater mapping using remote sensing or other indirect method.